Prevalence of illicit drug use in young sudden cardiac death patients; an Australian prospective cohort study. (3rd October 2022) - Trytell, A; Paratz, E D; Van Heusden, A; Zentner, D; Morgan, N; Smith, K; Thompson, T; James, P; Connell, V; Pflaumer, A; Semsarian, C; Ingles, J; et al.
Abstract: Background: Illicit drug use may accelerate coronary disease and cardiac hypertrophy or stimulate arrhythmias. Rates of illicit drug use in young sudden cardiac death (SCD) patients are uncertain. Purpose: To identify rates of illicit drug use in young SCD patients in Australia. Methods: A prospective multi-centre registry identified out of hospital cardiac arrest (OHCA) patients aged 1–50 years between April 2019 and April 2020. Clinical characteristics were compared between patients with and without illicit drug use (defined by toxicological results or reported regular use). Illicit drugs included stimulants such as amphetamine-type substances and cocaine, or non-stimulants such as heroin, cannabis and novel psychoactive substances (cathinones and synthetic cannabinoids). Results: 770 OHCAs occurred, with 555 patients undergoing forensic assessment. 287 patients had confirmed cardiac cause of OHCA, with 274 undergoing toxicological assessment and 79 (28.8%) having positive toxicology for illicit drugs (n=60) or reported regular drug use (n=19). An additional 121 patients experienced non-cardiac SCD due to illicit drug toxicity, resulting in a total of 200 patients (36.0% of OHCAs) with illicit drug use. Patients with SCD and illicit drug use were more commonly male (86.1% vs 72.3%, p=0.015), regular smokers (36.7% vs 21.5%, p=0.009), had cardiomegaly (76.5% vs 57.5%, p=0.007), and higher rates of coronary disease and cardiomyopathy (coronary disease 44.3% vs 33.3%, cardiomyopathy 30.4% vs 18.5%, p=0.003). Methamphetamines (n=42, 53.1%) were the most common illicit drug identified and polysubstance abuse occurred frequently (n=15, 19.0%). Conclusion: Approximately one-third of young SCD patients use illicit drugs, with high rates of polysubstance abuse. Illicit drug use in SCD patients is associated with coronary disease and cardiomyopathy. Funding Acknowledgement: Type of funding sources: None.